« Codivisation » des rites et « désordre » de l'interaction. Engagement et pare-engagement à l'ère de la distanciation. - Pascal Lardellier (Communiquer)
In the midst of the COVID-19 crisis, the ordeal of lockdown and social distancing reminds us starkly of the fundamental role played by rituals and everyday civilities in our relationships. It also proves once again the relevance of the conceptual tools handed down to us by Erving Goffman. Supported by survey evidence and deploying the theoretical framework of microsociology, this article analyses the upheavals introduced into our daily relationships by social distancing, barrier gestures and the widespread use of face-masks, all of which work to ‘desacralize’ interpersonal relations by challenging their ritual underpinnings.